A 4000-year debris flow record based on amphibious investigations of fan delta activity in Plansee (Austria, Eastern Alps) - Kiefer, Carolin; Oswald, Patrick; Moernaut, Jasper; Fabbri, Stefano Claudio; Mayr, Christoph; Strasser, Michael; Krautblatter, Michael (Earth Surface Dynamics, 2021)
The frequency of debris flows is hypothesized to have increased in recent decades with enhanced rainstorm activity. Geological evidence to test the relationship between climate and debris flow activity for prehistoric times is scarce due to incomplete sediment records, complex stratigraphy, and insufficient age control, especially in Alpine environments. In lacustrine archives, the link between onshore debris flow processes and the sedimentary record in lakes is poorly investigated. We present an amphibious characterization of alluvial fan deltas and a continuous 4000-year debris flow record from Plansee (Tyrol, Austria), combining light detection and ranging (lidar) data, swath bathymetry, and sediment core analyses. The geomorphic investigation of two fan deltas in different developmental stages revealed an evolutionary pattern of backfilling and new channel formation onshore, together with active subaqueous progradation on a juvenile fan delta, major onshore sediment deposition, and only few, but larger, subaqueous deposits on a mature fan delta. Geomorphic evidence for stacked and braided debris flow lobes, subaquatic landslide deposits, and different types of turbidites in sediment cores facilitated a process-based event identification, i.e. distinguishing between debris-flow-induced or earthquake-induced turbidites throughout the 4000-year sedimentary record. We directly correlate subaqueous lobe-shaped deposits with high backscatter signals to terrestrial debris flow activity of the last century. Moreover, turbidite thickness distribution along a transect of four cores allows us to pinpoint numerous events as being related to debris flow activity on a juvenile fan delta. In the sediment core, debris-flow-induced turbidites feature a more gradual fining upward grain size trend and higher TOC (total organic carbon) and delta C-13 values compared to earthquake-induced turbidites. The 4000-year event record contains 138 debris-flow-induced turbidites separated into four phases of similar debris flow activity (df phases). df phase 1 (similar to 2120 to similar to 2040 before the common era - BCE) reflects the second-highest observed event frequencies and is interpreted as being a postseismic landscape response. After a long period of long recurrence intervals without any outstanding increases in debris flow activity during df phase 2 (similar to 2040 BCE to similar to 1520 common era - CE), there are slightly increased event frequencies in df phase 3 (similar to 1520 to similar to 1920 CE). df phase 4 (similar to 1920 to 2018 CE) exhibits a drastic increase in debris flow activity, followed by the overall highest debris flow frequency of the whole record, which is about 7 times higher than during df phase 3. We show that the frequency increase in the debris-flow-induced turbidite record matches a previously postulated increase in debris flow events derived from aerial photography at Plansee in the last century. The triggering of debris flows is more controlled by short, intense precipitation than any other mass movement process, and we demonstrate that lacustrine debris flow records provide a unique inventory of hazard-relevant rainstorm frequencies over decades, centuries, and millennia. The presented increase in debris flow frequency since the start of the 20th century coincides with a twofold enhanced rainstorm activity in the Northern European Alps and, therefore, provides a novel technique for the systematic understanding of non-stationary debris flow frequencies in a changing climate.
CRIS-Team WoS Importer:2021-12-10

A one-million-year isotope record from siderites formed in modern ferruginous sediments - Vuillemin, Aurèle; Mayr, Christoph; Schuessler, Jan A.; Friese, André; Bauer, Kohen W.; Lücke, Andreas; Heuer, Verena B.; Glombitza, Clemens; Henny, Cynthia; von Blanckenburg, Friedhelm; Russell, James M.; Bijaksana, Satria; et al. (Geological Society of America Bulletin, 2023)
Ancient iron formations hold important records of environmental conditions during the Precambrian eons. Reconstructions of past oceanic systems require investigation of modern ferruginous analogs to disentangle water column and diagenetic signals recorded in iron-bearing minerals. We analyzed oxygen, iron, and carbon isotopes in siderite, a ferrous carbonate phase commonly used as an environmental proxy, from a 100-m-long record spanning a 1 Ma depositional history in ferruginous Lake Towuti, Indonesia. Combining bulk sediment and pore water geochemistry, we traced processes controlling siderite isotope signatures. We show that siderite oxygen isotope compositions (δ18O) reflect in-lake hydrological and depositional conditions. Low iron isotope values (δ56Fe) record water column oxygenation events over geological timescales, with minor diagenetic partitioning of Fe isotopes by microbial iron reduction after deposition. The carbon isotope compositions (δ13C) reflect the incorporation of biogenic HCO3 –, which is consistent with sediment organic matter remineralization lasting over ca. 200 ka after burial. Positive δ13C excursions indicate an increased production of biogenic methane that escaped the sediment during low lake levels. Diffusion across the sediment–water interface during initial formation of siderites tends to align the isotope signatures of bottom waters to those of pore waters. As microbial reduction of ferric iron and oxidation of organic matter proceed and saturate pore water conditions with respect to siderite, overgrowth on nuclei partially mutes the environmental signal inherited from past bottom waters over ca. 1 Ma. Because high depositional fluxes of ferric iron and organic matter in early oceans would have promoted similar microbial processes in ferruginous deposits prior to lithification, the environmental record contained in siderite grains can successively integrate depositional and early diagenetic signals over short geological timescales.
CRIS-Team Scopus Importer:2023-03-24

Benthic food web structure in the Comau fjord, Chile ( 42°S): Preliminary assessment including a site with chemosynthetic activity - Zapata-Hernández, Germán; Sellanes, Javier; Mayr, Christoph; Munoz, Práxedes (Progress in Oceanography, 2014)

Branched GDGT-based temperature calibrations from Central European lakes - Bauersachs, Thorsten; Schubert, Carsten J.; Mayr, Christoph; Gilli, Adrian; Schwark, Lorenz (Science of the Total Environment, 2024)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are common in lake sediments, where they are frequently employed to infer mean annual air temperatures (MAAT) or air temperatures of months above freezing (MAF) using the MBT'5Me lipid paleothermometer. The reliable reconstruction of such temperatures, however, requires robust calibration functions. Here, we investigated brGDGT distributions in surface sediments from 41 freshwater lakes located along an altitudinal gradient across the Alps (Central Europe) and spanning a MAAT range from 1.3 to 12.9 °C. Linear regression analysis demonstrates that fractional abundances of brGDGTs are strongly correlated with MAAT and MAF allowing to establish regional MBT'5Me-based transfer functions: MAAT (°C) = −2.19 + 31.91 × MBT'5Me (r2 = 0.72; RMSE = 1.51 °C) and MAF (°C) = 4.81 + 15.64 × MBT'5Me (r2 = 0.64, RMSE = 0.92 °C). Stepwise forward selection yielded the following, alternate temperature calibrations: MAAT (°C) = 7.11 + 67.66 × Ib – 13.54 × IIIa (r2 = 0.72; RMSE = 1.47 °C) and MAF (°C) = 5.19 + 16.22 × Ia (r2 = 0.66; RMSE = 0.98 °C). Our results demonstrate that the above calibration functions allow precise temperature reconstructions using lacustrine sediment records. However, our data also show that high-altitude lakes are more prone to warm bias and that lakes characterized by comparatively high abundances of 6-methyl brGDGTs show aberrant behaviors with temperature offsets up to ∼7 °C. Determining the IR6Me, as an independent control complementary to the MBT'5Me, is thus essential to validate the robustness of brGDGT-based temperature reconstructions of past climates. A cut-off value of 0.50 for the IR6Me is here proposed, after which MBT'5Me-reconstructed MAATs from lacustrine archives should be regarded as unreliable.
CRIS-Team Scopus Importer:2023-10-27
Keywords: IR; Lakes; Lipid paleothermometer; MBT'; Seasonality; Temperature calibrations

Cave finds indicate elk (Alces alces) hunting during the Late Iron Age in the Bavarian Alps - López Correa, Matthias; Pasda, Kerstin; Stojakowits, Philipp; Häck, Bernhard; Prieto, Jérôme; al-Fudhaili, Najat; Mayr, Christoph (E&G : Quaternary Science Journal, 2020)
The finding of a partially preserved elk skeleton from the Bavarian Alps is reported. Remnants of an adult male were found, together with skeletal elements of juvenile moose calves, at the base of a talus cone in the pit cave Stiefelschacht, next to Lenggries (southern Germany). The adult's bones exhibited anthropogenic traces like cut marks and were radiocarbon-dated to the Late Iron Age. A projectile hole in the left shoulder blade and cut marks on the bones are indicative of hunting and meat usage. The elk remains were associated with several wild and domestic species such as ungulates and hare but were not, however, accompanied by archaeological artefacts. Other archaeological sites of the Late Iron Age are so far not known within a distance of less than 30 km to the Stiefelschacht. While the presence of elk during prehistoric times in the Alps has already been known before, the finds and the location are unique in that they are the first evidence of elk hunting during the Late Iron Age in the northern Alp

Central Himalayan tree-ring isotopes reveal increasing regional heterogeneity and enhancement in ice mass loss since the 1960s - Singh, Nilendu; Shekhar, Mayank; Singh, Jayendra; Gupta, Anil K.; Bräuning, Achim; Mayr, Christoph; Singhal, Mohit (Cryosphere, 2021)
Tree-ring 18O values are a sensitive proxy for regional physical climate, while their 13C values are a strong predictor of local ecohydrology. Utilizing available ice-core and tree-ring 18O records from the central Himalaya (CH), we found an increase in east?west climate heterogeneity since the 1960s. Further, 13C records from transitional western glaciated valleys provide a robust basis for reconstructing about 3 centuries of glacier mass balance (GMB) dynamics. We reconstructed annually resolved GMB since 1743 CE based on regionally dominant tree species of diverse plant functional types. Three major phases became apparent: positive GMB up to the mid-19th century, the middle phase (1870?1960) of slightly negative but stable GMB, and an exponential ice mass loss since the 1960s. Reasons for accelerated mass loss are largely attributed to anthropogenic climate change, including concurrent alterations in atmospheric circulations (weakening of the westerlies and the Arabian Sea branch of the Indian summer monsoon). Multi-decadal isotopic and climate coherency analyses specify an eastward declining influence of the westerlies in the monsoon-dominated CH region. Besides, our study provides a long-term context for recent GMB variability, which is essential for its reliable projection and attribution.
CRIS-Team Scopus Importer:2021-01-15

Changing food webs before and during the Last Glacial Maximum based on stable isotopes of animal bone collagen from Lower Austria - Reiss, Lilian; Mayr, Christoph; Pasda, Kerstin; Einwögerer, Thomas; Händel, Marc; Lücke, Andreas; Maier, Andreas; Wissel, Holger (Journal of Quaternary Science, 2023)
We investigated palaeofood web structures using stable isotope analyses on animal bone collagen from four Upper Palaeolithic sites dated to the Early Gravettian (Krems-Hundssteig and Krems-Wachtberg: 33–31k cal a bp, Langenlois: 31–29k cal a bp) and to the Early Epigravettian (Kammern-Grubgraben: 24–20k cal a bp). In both periods, δ13C values show niche partitioning between hare, horse and mammoth on one side, and reindeer and ibex on the other, indicating different diets and habitats between both herbivore groups. The δ15N differences between carnivores and herbivores suggest a difference of one trophic level during the pre-Last Glacial Maximum (pre-LGM) period at the Early Gravettian sites and a tendency towards secondary carnivores during the LGM at Kammern-Grubgraben. δ15N values of pre-LGM mammoths are elevated in relation to other herbivores but shifted to the level of other herbivores in the LGM. A general δ15N value shift in herbivores of 3.3‰ from the pre-LGM to the LGM is related to climatic deterioration. This may have led to the disappearance of certain ecological niches and to a shift from broader to overlapping ecological herbivore niches shortly before the LGM, as demonstrated by SIBER analyses.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Epigravettian; Gravettian; niche partitioning; δ; δ

Chemical composition influences δ18O of chironomid larvae head capsules - Implications for climate reconstructions - Mayr, Christoph; Massaferro, Julieta; Wissel, Holger; Lücke, Andreas (Quaternary international, 2025)
Oxygen isotopes of chironomid head capsules in lake sediments have become an important proxy for climate reconstructions, especially for high-latitude regions. Various chemical pretreatments have been developed to remove organic and inorganic contaminants and to clean the head capsules prior to isotope analysis, but so far there is no standardised routine method to assess the purity of the isolated chitin. We present a dataset of oxygen isotope analyses of head capsules from seven lakes in southern South America. The head capsules were assigned to three different taxonomic groups of Chironomidae (Chironominae, Orthocladiinae, Tanypodinae) and to Ceratopogonidae. Orthocladiinae exhibited on average higher isotopic fractionation relative to lake water than the other taxonomic groups, although these differences were not statistically significant. Elemental analyses demonstrate that the oxygen content and molar N/O ratio of the head capsules have a larger influence on oxygen isotopic composition than the host water isotopic composition suggesting a strong influence of incomplete deproteination on oxygen isotope values of chironomid head capsules. This is backed up by an experimental approach with differently pretreated chironomids, which exhibits a strong correlation with N/O ratio presumably due to various degrees of deproteination. According to the N/O ratio, pure chitin was obtained after removal of the minerogenic fraction with a mixture of 10 % HF and 5 % HCl (16 h, 20 °C) and subsequent treatment with 5 % NaOH (2 h) and 7 % NaClO2 (10 h). In conclusion, we recommend using the N/O ratio for purity control and a critical assessment of different pretreatment methods to obtain pure chitin in future studies.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Chironomidae; Chitin; Climate proxy; Organic geochemistry; Sediment; Stable isotopes

Climate and environmental history of Laguna Polo, Santa Cruz, Southern Patagonia (49°S) since 1300 CE - Charqueño-Celis, Fernanda; Dubois, Nathalie; Zolitschka, Bernd; Pérez, Liseth; Mayr, Christoph; Massaferro, Julieta (Journal of Paleolimnology, 2024)
Patagonia is a unique area for climate studies, exposed to the strong Southern Hemisphere Westerly Winds (SWW) and modulated by the Southern Annular Mode (SAM). Patagonia is also affected by volcanic eruptions of the Andean Mountain Range, and is rich in lacustrine environments, which are ideal for paleocological and paleoclimatological reconstructions. Sediments of Patagonian lakes provide an excellent opportunity to study the responses of aquatic communities to major climatic and environmental events in still pristine freshwater ecosystems. Here, we present a high-resolution paleolimnological reconstruction using testate amoebae and chironomid assemblages and compare it with organic and inorganic sediment geochemistry (Ca, K, Ti, N, TOC, TOC/N, δ15N, δ13C) from a sediment core of Laguna Polo (49°S, Santa Cruz, Argentina) covering the last ca. 1300 years. Our results imply a warm-dry and productive environment from around 1300–1400 CE, a cold and less productive environment from ca. 1400–1700 CE, broadly corresponding to the Little Ice Age (LIA). The latter period is followed by high volcanic activity between ca. 1700 and 1960 CE. The tephra layers are known from other records in the vicinity and are preliminarily attributed to the eruptions of the adjacent Lautaro Volcano. A warm-stenothermic chironomid assemblage indicates a progressive increase in temperature in the most recent time after the last eruption, attributed to Lautaro Volcano in 1960 CE.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Chironomids; Lake sediments; Little Ice Age; Medieval Climate Anomaly; Testate Amoebae

Climate change-related growth improvements in a wide niche-breadth tree species across contrasting environments - Fajardo, Alex; Gazol, Antonio; Meynard, Paulo Moreno; Mayr, Christoph; Pastur, Guillermo J. Martinez; Peri, Pablo L.; Camarero, J. Julio (Annals of Botany, 2023)
Background and Aims The vulnerability and responsiveness of forests to drought are immensely variable across biomes. Intraspecific tree responses to drought in species with wide niche breadths that grow across contrasting climatically environments might provide key information regarding forest resistance and changes in species distribution under climate change. Using a species with an exceptionally wide niche breath, we tested the hypothesis that tree populations thriving in dry environments are more resistant to drought than those growing in moist locations. Methods We determined temporal trends in tree radial growth of 12 tree populations of Nothofagus antarctica (Nothofagaceae) located across a sharp precipitation gradient (annual precipitation of 500-2000 mm) in Chile and Argentina. Using dendrochronological methods, we fitted generalized additive mixed-effect models to predict the annual basal area increment as a function of year and dryness (De Martonne aridity index). We also measured carbon and oxygen isotope signals (and estimated intrinsic water-use efficiency) to provide potential physiological causes for tree growth responses to drought. Key Results We found unexpected improvements in growth during 1980-1998 in moist sites, while growth responses in dry sites were mixed. All populations, independent of site moisture, showed an increase in their intrinsic water-use efficiency in recent decades, a tendency that seemed to be explained by an increase in the photosynthetic rate instead of drought-induced stomatal closure, given that delta O-18 did not change with time. Conclusions The absence of drought-induced negative effects on tree growth in a tree species with a wide niche breadth is promising because it might relate to the causal mechanisms tree species possess to face ongoing drought events. We suggest that the drought resistance of N. antarctica might be attributable to its low stature and relatively low growth rate.
CRIS-Team WoS Importer:2023-05-26

Crystallization of ikaite and its pseudomorphic transformation into calcite: Raman spectroscopy evidence - Sánchez-Pastor, Nuria; Oehlerich, Markus; Astilleros, José Manuel; Kaliwoda, Melanie; Mayr, Christoph; Fernández-Díaz, Lurdes; Schmahl, Wolfgang (Geochimica Et Cosmochimica Acta, 2016)

Cultural evolution and environmental change in Central Europe between 40 and 15 ka - Maier, A.; Stojakowits, P.; Mayr, Christoph; Pfeifer, S.; Preusser, F.; Zolitschka, B.; Anghelinu, M.; Bobak, D.; Duprat-Oualid, F.; Einwögerer, T.; Hambach, U.; Händel, M.; et al. (Quaternary international, 2020)
The role of environmental change in the evolution of cultural traits is a topic of long-standing scientific debate with strongly contrasting views. Major obstacles for assessing environmental impacts on the evolution of material culture are the fragmentary nature of archaeological and – to a somewhat lesser extent – geoscientific archives and the insufficient chronological resolution of these archives and related proxy data. Together these aspects are causing difficulties in data synchronization. By no means does this paper attempt to solve these issues, but rather aims at shifting the focus from demonstrating strict chains of causes and events to describing roughly contemporaneous developments by compiling and comparing existing evidence from archaeology and geosciences for the period between 40 and 15 ka in Central Europe. Analysis of the archaeological record identifies five instances at around 33, 29, 23.5, 19, and 16 ka, for which evidence suggests an increased speed of cultural evolution. By comparing data from different geoscientific archives, we discuss whether or not these instances have common characteristics. We stress that common characteristics per se are no proof of causality; repeated co-occurrences of certain features over long periods of time, however, suggest that certain explanations may be more plausible than others. While all five cases roughly coincide with pronounced and rapid environmental changes, it is also observed that such conditions do not necessarily trigger major changes in the material culture. Increases and decreases in the diversity of cultural traits seem to be rather correlated with the overall demographic development. In compiling and comparing our data, we also identify periods with high need and potential for future research regarding the relation between environmental change and cultural evolution.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Cultural diversity; Cultural evolution; Demography; Environment; Last Glacial Maximum; Projectiles

Decoding a complex record of anthropogenic and natural impacts in the Lake of Cavazzo sediments, NE Italy - Polonia, Alina; Albertazzi, Sonia; Bellucci, Luca Giorgio; Bonetti, Carla; Bonetti, Jarbas; Giorgetti, Giulia; Giuliani, Silvia; Correa, Matthias López; Mayr, Christoph; Peruzza, Laura; Stanghellini, Giuseppe; Gasperini, Luca (Science of the Total Environment, 2021)
The Lake of Cavazzo is a natural, lacustrine basin in the Friuli-Venezia Giulia region (NE Italy), which occupies a fluvio-glacial suspended valley of the Tagliamento river, at the southern front of the Alpine chain. The lake formed after the melting of major glacial tongues at the end of the Last Glacial Maximum, and has been affected in recent years by natural and anthropogenic events, with economic, cultural and environmental consequences. According to local witnesses, the lake environment has changed dramatically after the 1950s, when the basin was connected to a hydroelectric power plant collecting waters from a wider catchment area, as it served as its final discharge basin. In this work, based on a densely-spaced grid of high-resolution seismic reflection profiles complemented by sediment cores, we analysed the uppermost lake stratigraphy, highlighting major changes occurring at a decadal scale. Our main purpose is to verify whether and how the lake sediments record the transition from pristine/natural to artificial conditions, as well as the effects of multiple natural impacts including the 1976–77 Friuli earthquake sequence. The results of our analysis suggest varying environmental conditions of the lake after the 1950s indicated by changing sediment mineralogy, increased deposition of allochthonous clastic sediments, and recurrent episodes of anoxic conditions at the lake's floor, likely triggered by hyperpycnal flows derived from the hydroelectric power plant discharges. We also observe that the effects of the 1976–77 seismic sequence are recorded in the lake as resedimented levels, likely due to shaking, in situ deformation, landslides, and turbidity currents. Our results stress the importance of lacustrine environments as efficient recorders of anthropogenic and natural events.
CRIS-Team Scopus Importer:2021-06-18
Keywords: 1976 Friuli earthquakes; Carnia region; Eastern Alps; Hydroelectric power plant; Lacustrine seismo-turbidite

Dickdellia on Colossendeis: Testing ectoparasitism with stable isotopes - Melzer, Roland R.; Lehmann, Tobias; Mayr, Christoph (Antarctic Science, 2020)
CRIS-Team Scopus Importer:2020-04-14

Diet and species-specific oxygen isotope relationship and isotope spacing between structural carbonate and phosphate in archaeological mammalian bones - Goehring, Andrea; Von Carnap-Bornheim, Claus; Hilberg, Volker; Mayr, Christoph; Grupe, Gisela (Archaeological and Anthropological Sciences, 2019)
Stable oxygen isotopes of bone structural carbonate (δ 18 O carbonate ) and phosphate (δ 18 O phosphate ) are frequently used for paleoclimatological and paleoenvironmental studies. In several studies, the more conveniently measureable δ 18 O carbonate values are measured, and δ 18 O phosphate values are approximated according to published regressions. We studied a variety of individuals (n = 101) of different wild and domesticated mammal species (n = 19) from the Viking Haithabu and medieval Schleswig sites in Northern Germany and demonstrated that a generalized relationship between δ 18 O carbonate and δ 18 O phosphate with a fixed value for oxygen isotope spacing (Δδ 18 O) is potentially error-prone. The Δδ 18 O values of our data set differ considerably from the commonly applied, fixed value of about 9 ‰ with values ranging from 3.8 to 8.1 ‰ (μ = 6.1 ‰ ± 0.9 ‰). Statistically significant differences in the Δδ 18 O values and marked differences in linear models established for the relationship between δ 18 O carbonate and δ 18 O phosphate are related to species-specific diet and physiology. Therefore, such species-specific particularities must not be neglected. We conclude that this variability does no longer permit an approximation of oxygen isotope values of bone phosphate from carbonate, because δ 18 O phosphate values approximated in such a way are highly error-prone. Parallel analyses of both δ 18 O carbonate and δ 18 O phosphate values are therefore indispensable.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Apatite; Stable isotopes; δ; Δδ

Environmental change in the vicinity of the Neolithic wetland settlement Pestenacker (S-Germany) during the last 6600 years - Mayr, Christoph; Matzke-Karasz, Renate; Manthe, Pierre; Arnold, Johannes; Hänfling, Carolin; Hilber, Joachim; Spitzenberger, Dominik; Schmid, Wolfgang; Schönfeld, Guntram (Journal of Archaeological Science, 2015)
Pestenacker and the adjacent Neolithic wetland sites Unfriedshausen and Pestenacker-Nord in southern Germany belonged to the Altheim culture from around 5750-5350 years cal. BP. In contrast to contemporaneous pile dwellings, the houses of Pestenacker were constructed at ground level in a wetland environment. Only little is known about the environmental and hydrological conditions in the direct vicinity of the settlement and how they changed in time. To find detailed answers to these questions, stratigraphy, sedimentology, microfossils, geochemistry and stable isotopes of a sediment profile immediately to the west of the settlement were studied. An age model comprises five radiocarbon dates and dates the base of the profile to about 6600 years cal. BP. Ostracods and aquatic gastropods were frequent only in the basal part of the profile. Ostracod taxa typical for open-water conditions point to higher humidity especially at 6120-5860 years cal. BP and 5750-5370 years cal. BP. Sedimentology and organic carbon isotope data confirm this observation. Thereafter open-water habitats disappeared, while increasing numbers of non-aquatic gastropods occur and soil formation is indicated by elevated δ15N values. We conclude that during the time of settlement an open water body existed near-by that disappeared shortly after the settlement was abandoned. However, the spatial extent of this water body still remains to be clarified.
Keywords: Altheim culture; Gastropods; Ostracods; Palaeoenvironment; Sediment profile; Stable isotopes; Wetland settlement

Environments at the MIS 3/2 transition in the northern Alps and their foreland - Stojakowits, Philipp; Mayr, Christoph; Ivy-Ochs, Susan; Preusser, Frank; Reitner, Jürgen M.; Spötl, Christoph (Quaternary international, 2020)
This paper reviews the current state of knowledge about environmental changes at the MIS 3/2 transition in the northern Alps and their foreland, covering the time frame from 35 to 25 ka. Lake and peat deposits, cave sediments, loess and glacial deposits are presented and the response of their biotic and abiotic proxies to climate change is discussed. During late MIS 3, interstadial conditions, albeit weak, occurred at c. 36–32 ka. At climatically favourable sites, small patches of trees (mainly Pinus and some Betula) existed together with some shrubs. The environmental conditions during late MIS 3 are also reflected by a boreal brown soil horizon, a cambisol called Lohne soil, found in many loess sequences. Subsequently, the environmental conditions became harsher as shown by the proxy data. From c. 30 ka onwards the absence of pedogenesis sensu stricto and the plant assemblages point to an Arctic climate in the northern Alpine foreland. Accentuating, glaciers advanced beyond the northern limit of the Alps around the MIS 3/2 boundary and reached their maximum extent in the foreland at about 25 ka.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Last glacial maximum; Molluscs; Palaeo-environment; Palaeosol; Vegetation response

Evaluation of geochemical proxies and radiocarbon data from a loess record of the Upper Palaeolithic site Kammern-Grubgraben, Lower Austria - Reiss, Lilian; Stüwe, Christian; Einwogerer, Thomas; Handel, Marc; Maier, Andreas; Meng, Stefan; Pasda, Kerstin; Simon, Ulrich; Zolitschka, Bernd; Mayr, Christoph (E&G : Quaternary Science Journal, 2022)
Two loess sections from the Upper Palaeolithic site of Kammern-Grubgraben (Lower Austria) were analysed to test geochemical proxies, as well as radiocarbon data of different components, for their reliability and consistency in an archaeological context. Only a reliable basal age (28.9-27.8 ka cal BP) was obtained from charcoal fragments derived from a tundra gley underlying the archaeological horizons and assigned to Greenland Interstadials 3 or 4. Grain size, organic and inorganic geochemistry, and stable isotopes of the fine organic fraction (delta C-13(org)) and of rhizoconcretions (delta C-13, delta O-18) were analysed to provide information on palaeoenvironmental conditions. Low-resolution geochemical and sedimentological analyses document a humidity-related variability, while delta C-13(org) values indicate predominant C-3 vegetation. High-resolution elemental variations derived from X-ray fluorescence scanning exhibit increasing Ca and decreasing Fe and Ti values, indicating drier conditions towards the top. Secondary pedogenic carbonate concretions provide post-sedimentary (Holocene) ages and are not suitable for assessing climate and environmental changes for the Palaeolithic.
CRIS-Team WoS Importer:2022-03-18

Evidence for sea spray effect on oxygen stable isotopes in bone phosphate — Approximation and correction using Gaussian Mixture Model clustering - Göhring, Andrea; Mauder, Markus; Kröger, Peer; Mayr, Christoph; von Carnap-Bornheim, Claus; Hilberg, Volker; Grupe, Gisela (Science of the Total Environment, 2019)
Palaeobiodiversity research based on stable isotope analysis in coastal environments can be severely hampered by the so-called “sea spray” effect. This effect shifts the isotopic signal of terrestrial individuals towards too marine values. It is commonly agreed upon that sea spray influences sulphur stable isotopes. However, we were able to approximate a remarkable sea spray effect also in carbon and oxygen stable isotopes of bone carbonate previously. In the present study we could approximate a minimum sea spray effect of about 13.9% even present in oxygen isotope values of bone phosphate, which was validated by Gaussian Mixture Model (GMM) clustering. This approximated value is by some magnitudes smaller than the minimum sea spray effect approximated for both δ 13 C carb and δ 18 O carb , and quite close to the sea spray detected for δ 34 S coll in a previous study. It may therefore be interpreted as purer minimum sea spray signal compared to the approximation in bone carbonate. Furthermore, detection of sea spray in δ 18 O phos can serve as additional validation of the effect present in bone carbonate, which is more prone to diagenetic alteration compared to bone phosphate. Moreover, the presence of the sea spray effect in both δ 18 O carb and δ 18 O phos demonstrates that sea spray can be taken up by terrestrial mammals not only via food (δ 18 O carb ) but also via drinking water (δ 18 O phos ). Finally, this study once more confirmed that calculation of δ 18 O phos from δ 18 O carb values using a fixed oxygen isotope spacing (Δδ 18 O) can be highly misleading, especially in coastal environments affected by sea spray.
CRIS-Team Scopus Importer:2019-05-10
Keywords: Bone apatite; Cluster analysis: δ18O; Δδ18O; GMM; Oxygen isotope spacing

First indications of seasonal and spatial variations of water sources in pine trees along an elevation gradient in a Mediterranean ecosystem derived from δ18O - Szymczak, Sonja; Barth, Johannes; Bendix, Jörg; Huneau, Frédéric; Garel, Emilie; Häusser, Martin; Juhlke, Tobias; Knerr, Isabel; Santoni, Sébastien; Mayr, Christoph; Trachte, Katja; van Geldern, Robert; et al. (Chemical Geology, 2020)
Water availability is the most important factor for the vitality of forest ecosystems, especially in dry environments. The Mediterranean region is one of the hotspots of future climate change; therefore, data on the water cycle are urgently needed. We measured oxygen isotope compositions in creek water, precipitation, stem water, needle water, and tree-ring cellulose over one growing season to establish the relationship between isotope compositions in different compartments along a fractionation pathway. We analyzed plant material from pine trees (Pinus nigra J.F. Arn subsp. laricio (Poiret) Maire var. Corsicana Hyl. and Pinus pinaster Aiton) at five locations along an elevation gradient from sea level to 1600 m asl. We traced back the oxygen isotope composition from source to sink in tree-ring cellulose in order to identify the water sources used by the trees, and to quantify the extent of isotope fractionation processes. Our results showed that the trees used different water sources over the course of the growing season, ranging from winter snow meltwater to summer precipitation at higher sites and deep soil water reservoirs at coastal sites. Needle water enrichment was higher at higher elevation sites than at coastal locations, highlighting the importance of site-specific climate conditions on the isotopic composition values in tree material. Water availability seems to be most restricted at the highest site, making these trees most vulnerable to climate change.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Needle water enrichment; Oxygen isotopes; Pinus nigra; Pinus pinaster; Water source; Xylem water

Groundwater in the Na’ur area, Jordan: movement and pollution under changes in landscape uses - Alsawaeir, Dana; Abu-Jaber, Nizar; Lücke, Andreas; Mayr, Christoph; Lucke, Bernhard (Environmental Earth Sciences, 2024)
The Cretaceous karstified limestone aquifers in northwestern Jordan are the major source of water in the area. The study area lies to the south of Amman in a mostly rural area on the margin of the Jordan Valley Rift. Stable isotope and tritium data indicate that this is a recharge zone. Groundwater flows both towards the rift, where the springs emanate, and towards the east into the plateau region, possibly emanating in the Wadi Sirhan area in eastern Jordan. The geochemical analyses show that significant pollution is affecting the water in the more populated areas, while pollution in the agricultural areas occurs to a lesser extent. Thus, while the karst aquifers in the area receive recharge from a significantly larger catchment area, it is also vulnerable to pollution due to local mismanagement. Expanded urbanization not taking this into consideration will lead to increased groundwater degradation in the future.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Geochemical; Isotopes; Pollution; Tritium

High-resolution geochemical record of environmental changes during MIS 3 from the northern Alps (Nesseltalgraben, Germany) - Mayr, Christoph; Stojakowits, Philipp; Lempe, Bernhard; Blaauw, Maarten; Diersche, Volker; Grohganz, Madleen; Correa, Matthias López; Ohlendorf, Christian; Reimer, Paula; Zolitschka, Bernd (Quaternary Science Reviews, 2019)
Ravine slopes at the recently discovered Nesseltalgraben site in southeastern Germany provide a unique last glacial sediment record for the Northern Calcareous Alps. The 21 m-long profile is dominated by fine-grained lacustrine-palustrine sediments overlain by several metres of glacifluvial gravels and lodgement tills of the Last Glacial Maximum and underlain by a diamicton. The age model includes 29 radiocarbon analyses and one paleomagnetic anomaly (Laschamp event) together providing a modelled age range from c. 59 to 29.6 ka cal BP, i.e. Marine Isotope Stage (MIS) 3. Apart from a description of the lithofacies, X-ray-fluorescence (XRF) scanning and elemental analyses provide high-resolution records of the geochemical composition. Multivariate analyses of XRF data separate Ca from other major elements. Carbonate contents, represented by Ca and total inorganic carbon, reach maxima in repeatedly occurring calcareous silty to sandy layers and are related to glacigenic origin. These indicate repeated inner-alpine local glaciations during stadials of MIS 3. Scanning electron microscopy and XRF data confirm the detrital origin of these layers. In contrast, organic matter and elements more resistant to chemical weathering (Si, Ti, Zr) accumulated during interstadials and concurrently elevated Rb/Sr ratios indicate intensified weathering. The high-frequency proxy variations determined for Nesseltalgraben reflect interstadial-stadial climate variability comparable with oxygen-isotope records from Greenland ice cores and Alpine speleothems. Thus, Nesseltalgraben is among the very few independently dated sediment records from continental Europe covering the entire MIS 3 and reflecting the full Dansgaard-Oeschger climate variability.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Central Europe; Dansgaard-Oeschger cycles; Glaciation; Grain-size analyses; Greenland interstadials; Lacustrine-palustrine sediment; Middle Würmian; Paleoclimatology; Pleistocene; Radiocarbon dating

Historical eruptions of Lautaro Volcano and their impacts on lacustrine ecosystems in southern Argentina - Mayr, Christoph; Smith, Rebecca E.; García, M. Luján; Massaferro, Julieta; Lücke, Andreas; Dubois, Nathalie; Maidana, Nora I.; Meier, Wolfgang; Wissel, Holger; Zolitschka, Bernd (Journal of Paleolimnology, 2019)
Lacustrine sediment sequences were obtained from Lagunas Verde and Gemelas Este, two small lakes located east of the southern Patagonian Ice Field and close to the village of El Chaltén, in Argentinian Patagonia. Four tephra layers were identified in each of the short sediment sequences and characterised using individual glass-shard tephra chemistry to determine provenance. Bulk sediment geochemistry and diatom assemblages were analysed to understand the impact of the tephra deposits on the lake ecosystems. Age-depth models for the cores were established by 137Cs and 210Pb dating. Tephra deposits in Laguna Gemelas Este were dated to AD 1986–1998, 1943–1968, 1927–1955, and 1849–1892, and the tephra deposits in Laguna Verde were dated to AD 1940–1970, 1888–1934, 1871–1920, and 1536–1669, the latter interval determined by extrapolation. All tephras had similar geochemical composition and originated from volcanoes in the northern Austral Volcanic Zone. Tephra units were attributed to known historical eruptions and all but one, most likely, were from Lautaro Volcano (49°01′S; 73°33′W). The age of the youngest tephra (AD 1986–1998) from Laguna Gemelas Este points to Viedma Volcano (49°22′S; 73°19′W) as a possible source. Volcanic eruptions had a larger impact on Laguna Verde than on Laguna Gemelas Este, as expressed by changes in δ15N values and diatom communities during tephra deposition. These shifts are explained by perturbations of the nitrogen cycle in the lake, associated with shifts in lacustrine primary production. Primary producers may have been affected by increased water turbidity caused by the ash fall, and consequently, used less nitrogen. Diatom assemblages in Laguna Verde showed marked reductions in numbers of planktonic/tychoplanktonic taxa, in favour of epiphytic/benthic diatom taxa, when tephra was deposited. This contrasts with Laguna Gemelas Este, in which epiphytic/benthic diatom species were generally more abundant and decreases in abundances of planktonic/tychoplanktonic taxa were not as strongly linked to tephra layers as in Laguna Verde. At Laguna Gemelas Este, flatter relief, greater fetch and/or drier climate may have contributed to generally less ecosystem variability, resulting in seemingly less environmental response to volcanic eruptions than in Laguna Verde.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Diatoms; Geochemistry; Northern Austral Volcanic Zone; Patagonia; Stable isotopes; Tephra

Holocene history of human impacts inferred from annually laminated sediments in Lake Szurpity, northeast Poland - Kinder, Malgorzata; Tylmann, Wojciech; Bubak, Iwona; Filoc, Magdalena; Gasiorowski, Michal; Kupryjanowicz, Miroslawa; Mayr, Christoph; Sauer, Laurentius; Völlering, Ulrich; Zolitschka, Bernd (Journal of Paleolimnology, 2019)
Annually laminated lake sediments provide high-resolution and accurate timescales for reliable paleoenvironmental reconstructions. We investigated human activity in a low-human-impact region of Poland, taking advantage of varved sediments from Lake Szurpily, which span the last 8200 years. Multiple sediment variables indicated that catchment evolution and lacustrine responses, mainly to changes in forest cover, were divided into four phases. Because of sparse or only seasonal occupation of settlements in NE Poland, human impact in the region was insignificant until ca. 939 +/- 55 BC (lacustrine phase I). During Phase II (939 +/- 55 BC-AD 1392 +/- 38), we recorded an increase in human indicators, reflecting the direct influence of a Yatvingian community. Afterwards, between AD 1392 +/- 38 and 1770 +/- 30 (phase III), permanent settlements and agricultural land use stabilized. The beginning of the last period (phase IV) was clearly identified by all sediment variables, which responded simultaneously to local human activities. Disappearance of laminae from AD 1858 +/- 22 until about AD 1997 indicated disturbance of pre-existing, stable depositional conditions, followed by environmental recovery in the last 20 years. Such recovery may have been related to recent socio-economic changes and establishment of a park that reduced human influence on the lake.
CRIS-Team WoS Importer:2019-04-23

Holocene palaeoceanographic history of the western South Atlantic - García Chapori, Natalia; Laprida, Cecilia; Lo Prete, Daniel; Chiessi, Cristiano M.; Mayr, Christoph; Violante, Roberto A. (Journal of South American Earth Sciences, 2022)
Although the circulation of the western South Atlantic tightly controls the meridional heat and salt transport, our knowledge about its long-term past changes is still fragmented and sparse. While many studies focused their attention on the last glacial and deglaciation periods, Holocene studies mostly lack of an integrated analysis from the subtropical and midlatitude regions. The analysis of selected regionally distributed palaeoceanographic records along the western South Atlantic between 27° and 39°S reveals that, although weaker in amplitude than the dramatic shifts of the last glacial cycle, the Brazil-Malvinas Confluence region showed substantial changes throughout the Holocene. The shift in the location of both southern and northern source waters in the Atlantic implied a strengthening of the Southern Atlantic Meridional Overturning Circulation since the Mid-Holocene. This, together with the progressive southward displacement of the Brazil-Malvinas Confluence confirms the progressive weakening of the Atlantic Meridional Overturning Circulation towards the preindustrial times.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Holocene; Paleoceanography; Paleoclimate; Western South Atlantic

Identification and quantification of the sea spray effect on isotopic systems in α-cellulose (δ13C, δ18O), total sulfur (δ34S), and 87Sr/86Sr of European beach grass (Ammophila arenaria, L.) in a greenhouse experiment - Göhring, Andrea; Hölzl, Stefan; Mayr, Christoph; Strauss, Harald (Science of the Total Environment, 2023)
The sea spray effect can severely influence the isotopic signature of terrestrial individuals in coastal regions. To further specify this effect, beach grass was grown in a greenhouse under controlled environmental conditions and sprayed with mineral salt solution containing different mineral salts but only traces of NaCl (group 1). Another group of plants was sprayed with salty water from the Schlei inlet and the Baltic Sea, respectively (group 2). Control plants were only sprayed with tap water. Isotope analyses were conducted on the unwashed and washed plants (δ13Ccellulose, δ18Ocellulose, δ34Stotal S, 87Sr/86Sr), soil (δ18Osulfate, δ34Ssulfate, 87Sr/86Sr), and spray as well as irrigation water (δ18Osulfate, δ34Ssulfate, 87Sr/86Sr). Moreover, elemental analyses were performed on the water samples. The sea spray effect was visible in all isotopic systems under study. The uptake of SO42−, HCO3−, and Sr2+ directly affected plants of group 1, while plants of group 2, sprayed with salty water, additionally showed salinity stress in the case of α-cellulose and total sulfur due to biochemical reactions of the plants. Very high concentrations in HCO3− or SO42− also affected the plants' isotopic signatures. The impact of the sea spray and additional stress reactions were quantified. Our study is the first experiment creating an artificial sea spray effect in a greenhouse. This experiment for the first time enables the identification and quantification of the sea spray effect in environmental samples. The marine signature taken up by the plants and recorded by the investigated isotopic systems is apparently high and should have an impact on the isotopic fingerprints of animal consumers at the coast, as evidenced for archaeological animals from the Viking Haithabu and the early medieval Schleswig sites located close to the Baltic Sea. This result demonstrates the potential of greenhouse experiments as an isotopic predictor of the past local sea spray effect.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Aerosol; Biochemistry; Cellulose; Coast; Leaf; Marine; Plant metabolism; Root; Seawater; Strontium; Sulfate

Impact of climatic extremes on Alpine ecosystems during MIS 3 - Stojakowits, Philipp; Mayr, Christoph; Lücke, Andreas; Wissel, Holger; Hedenäs, Lars; Lempe, Bernhard; Friedmann, Arne; Diersche, Volker (Quaternary Science Reviews, 2020)
The effects of climatic extremes on Alpine ecosystems, such as in the last glacial period, are poorly understood. The recently discovered Nesseltalgraben site is currently the best dated and most complete high-resolution sedimentary sequence in the northern Alps covering the Marine Isotope Stage (MIS) 3 around 59-28 calibrated kiloyears before present (ka cal BP). The MIS 3 is a period with frequent climatic fluctuations known as Dansgaard-Oeschger cycles or Greenland interstadials-stadials. Here, we present pollen assemblages, bryophyte macrofossils, and stable isotopes (δ2H, δ13C, δ18O) from the Nesseltalgraben to elucidate palaeoenvironments and palaeoclimatic variability during that period. In addition to bulk sedimentary cellulose, also cellulose extracted from fossil wood, monocots, and bryophytes was analysed isotopically. Among the terrestrial pollen, Poaceae and arboreal pollen show an antithetic behaviour reflecting interstadial-stadial variations. Arboreal pollen are dominated by Pinus sylvestris-type, with admixtures of Picea, Betula, Alnus, and Salix. The arboreal pollen record exhibits several maxima indicating milder climatic conditions tentatively assigned to Greenland interstadials 17–14, 12/11, 8, and 6. During Heinrich events 5 and 4, the arboreal pollen record shows distinct minima underlining a severe impact of these events on regional climate and vegetation. Bryophyte assemblages show predominant wetland conditions at the site during the entire MIS 3. The sudden occurrence of the bryophyte Drepanocladus turgescens after 31.6 ka cal BP indicates a change from a fen to a frequently drying wetland environment. This habitat change is presumably linked to enhanced glaciofluvial action caused by glaciers approaching the site. Carbon, hydrogen, and oxygen stable isotope records of bulk sedimentary cellulose exhibit comparably stable conditions from 59 until 52 ka cal BP and increased values around 51 ka cal BP followed by a period of almost absent cellulose until 39 ka cal BP. Thereafter, and lasting until 30 ka cal BP, bulk sedimentary cellulose isotope records (δ2H, δ13C, and δ18O) reveal strongly fluctuating values. These isotope variations are interpreted as variable mixtures between terrestrial lignified plants and monocots on the one, and wetland bryophyte sources on the other hand. A strong negative isotope excursion in the bulk sedimentary and the bryophyte cellulose records around 36.4 ka cal BP is contemporaneous with maximum Cyperaceae pollen and best explained by progressively waterlogged soils due to permafrost. The rise in the bryophyte δ18O record thereafter, accompanied by likewise increasing δ13C values, most likely indicates an enhanced evaporation of source waters.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bryophytes; Cellulose; Dansgaard-Oeschger events; Greenland interstadials; Heinrich events; Nesseltalgraben; Northern Alps; Pollen; Stable isotopes; Vegetation dynamics

Impact of human activities and climate on Lake Morenito, Northern Patagonia, Argentina - Mauad, Melina; Mayr, Christoph; Grassl, Teresa; Dubois, Nathalie; Serra, Maria Noel; Massaferro, Julieta (Hydrobiologia, 2019)
Lake Morenito located in the Argentinean Patagonia has been exposed to climatic, volcanic, and anthropogenic impacts for the last decades. In particular, the damming of the lake and the eruption of the Calbuco/Puyehue Volcanoes in AD 1960 played an important role in the lake’s history. A 80-cm-long sediment core from Lake Morenito spanning more than 100 years was studied for chironomids, stable isotopes, and organic geochemistry to investigate how natural and anthropogenic stressors impacted the lake. Chironomid assemblages display large changes around AD 1950, with the appearance of the warm-adapted Chironomus and the replacement of Apsectrotanypus by Ablabesmyia, indicating a shift to warmer conditions. By that time and up to the present, an increasing trend of δ15N coupled with a decrease of δ13C points to shifts in the carbon and nitrogen cycles associated with human activities. It is evident that the onset of human activities during the 1950s following by the lake damming in AD 1960 had significant effects on the chironomid assemblages and the geochemical composition of sediments which is reflected in the progressive deterioration of the lake ecosystem.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Chironomid assemblages; Human impact; Organic geochemistry; Paleolimnology; Patagonia

Intensified Southern Hemisphere Westerlies regulated atmospheric CO2 during the last deglaciation - Mayr, Christoph; Lücke, Andreas; Wagner, Sebastian; Wissel, Holger; Ohlendorf, Christian; Haberzettl, Torsten; Oehlerich, Markus; Schäbitz, Frank; Wille, Michael; Zhu, Jiayun; Zolitschka, Bernd (Geology, 2013)

Isotopic Map of the Inn-Eisack-Adige-Brenner-Passage and its Application to Prehistoric Human Cremations - Toncala, Anita; Söllner, Frank; Mayr, Christoph; Hölzl, Stefan; Heck, Karin; Wycisk, Dominika; Grupe, Gisela (Across the Alps in Prehistory, 2017)

Lateglacial and Holocene climatic changes in south-eastern Patagonia inferred from carbonate isotope records of Laguna Potrok Aike (Argentina) - Oehlerich, Markus; Mayr, Christoph; Gussone, Nikolaus; Hahn, Annette; Hölzl, Stefan; Lücke, Andreas; Ohlendorf, Christian; Rummel, Susanne; Teichert, Barbara; Zolitschka, Bernd (Quaternary Science Reviews, 2015)

Late Holocene hydrologic changes in northern New Zealand inferred from stable isotope values of aquatic cellulose in sediments from lake Pupuke - Heyng, Alexander; Mayr, Christoph; Lücke, Andreas; Wissel, Holger; Striewski, Bernd (Journal of Paleolimnology, 2014)

Late Holocene hydrology inferred from lacustrine sediments of Laguna Cháltel (southeastern Argentina) - Ohlendorf, Christian; Fey, Michael; Massaferro, Julieta; Haberzettl, Torsten; Laprida, Cecilia; Lücke, Andreas; Maidana, Nora; Mayr, Christoph; Oehlerich, Markus; Ramón-Mercau, Josefina; Wille, Michael; Corbella, Hugo; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)

Linking Oxygen Isotopes of Animal-Bone Phosphate with Altimetry: Results from Archaeological Finds from a Transect in the Alps - Mayr, Christoph; Grupe, Gisela; Toncala, Anita; Lihl, Christina (Isotopic Landscapes in Bioarchaeology, 2016)

Middle and Late Holocene paleotemperatures reconstructed from oxygen isotopes and GDGTs of sediments from Lake Pupuke, New Zealand - Heyng, Alexander; Mayr, Christoph; Lücke, Andreas; Moschen, Robert; Wissel, Holger; Striewski, Bernd; Bauersachs, Thorsten (Quaternary international, 2015)
Quantitative Holocene temperature reconstructions for Southern Hemisphere terrestrial environments are still restricted to few records, and multi-proxy methods are rarely applied to the same system. Here, we test the applicability and comparability of temperature reconstructions inferred from different methodological approaches. We combined sedimentary cellulose and diatom oxygen isotope data from Lake Pupuke (North Island New Zealand) to derive a record of lake water temperatures. This record is complemented with mean annual air temperatures derived from the branched GDGT index MBT measured on the same sedimentary record. The datasets of both reconstructions show little temperature variation for the period 1320e7110 cal. BP. The exceptions are a warmer period culminating between 1700 and 1600 cal. BP reflected in both proxies and centennial-scale intervals with cooler water temperatures at 3380 and 2750 cal. BP recorded in the oxygen-isotope-based temperature reconstruction but not in the MBT-inferred air temperature estimates. We suggest that variations in lake circulation are the likely reason for deviations between temperature reconstructed from different proxies.
Keywords: Paleotemperatures; New Zealand; Holocene; Oxygen isotopes; Biogenic silica; Branched GDGTs

Multidisciplinary dataset for geological and environmental studies in the lake of Cavazzo (Southern Alps) - Polonia, Alina; Albertazzi, Sonia; Bellucci, Luca Giorgio; Bonetti, Carla; Bonetti, Jarbas; Gallerani, Andrea; Giorgetti, Giulia; Giuliani, Silvia; López Correa, Matthias; Mayr, Christoph; Miserocchi, Stefano; Peruzza, Laura; et al. (Data in Brief, 2021)
The present dataset was collected to evaluate the environmental stressors on a lacustrine basin in the Eastern Alps of glacial origin that has been affected in recent years by natural and anthropogenic events such as the construction of a hydroelectric power plant and a series of strong earthquakes during 1976-1977. We collected sediment cores in different sites from the lake margins to the depocenter and performed a multiproxy analysis of sediment sample to highlight lake stratigraphy and major changes occurring at a decadal scale (Polonia et al., [1]). The integrated analyses of sedimentological, geochemical, isotopic, mineralogical and micropaleontological analyses aimed at reconstructing changes in sediment composition and define the triggering mechanisms of altered environmental conditions. The dataset demonstrates that evaluating ex post the effects of artificial modification in a natural environment during relatively long time spans (decades) can provide important insights for managing and protection strategies in similar environments worldwide
CRIS-Team Scopus Importer:2021-07-02
Keywords: Anthropogenic impacts; Earthquakes; Hydroelectric power plant; Lacustrine seismo-turbidite; Seismic hazard

Multi-isotope fingerprints of recent environmental samples from the Baltic coast and their implications for bioarchaeological studies - Göhring, Andrea; Hölzl, Stefan; Mayr, Christoph; Strauss, Harald (Science of the Total Environment, 2023)
Stable isotopes in coastal regions are influenced by the so-called sea spray effect which masks the actual terrestrial isotope fingerprint with a marine isotope signal. The sea spray impact on plants was investigated by analyzing different stable isotope systems (δ13Ccellulose, δ18Ocellulose, δ18Osulfate, δ34Ssulfate, δ34Stotal S, δ34Sorganic S, 87Sr/86Sr) in recent environmental samples (plants, soil, water) collected close to the Baltic Sea. All these isotopic systems are influenced by the sea spray, either by the uptake of ions (HCO3−, SO42−, Sr2+) of marine origin, thus exhibiting a marine isotopic signature, or by biochemical reactions associated with, e.g., salinity stress. A shift towards seawater values is observed for δ18Osulfate, δ34S, and 87Sr/86Sr. Cellulose becomes enriched in 13C and 18O due to sea spray, further enhanced (δ13Ccellulose) or mitigated (δ18Ocellulose) by salinity stress. The effect differs both regionally and seasonally, probably as a result of, e.g., differences in wind strength or prevailing wind direction, as well as between plants collected only few meters apart, in either the open field or at more wind-protected sites, reflecting samples more or less influenced by sea spray. The stable isotope data of recent environmental samples are compared to previously analyzed archaeological bone samples of animals from the Viking Haithabu and Early Medieval Schleswig sites located close to the Baltic Sea. Potential regions of origin can be predicted based on the magnitude of the (recent) local sea spray effect. This enables the identification of probably non-local individuals. The insights into sea spray mechanisms, biochemical reactions in plants, as well as seasonal, regional, and small-scale differences in stable isotope data will help to interpret multi-isotope fingerprints at coastal sites. Our study demonstrates the usefulness of environmental samples for bioarchaeological studies. Moreover, the detected seasonal and small-scale differences require adjusted sampling strategies for, e.g., isotopic baselines in coastal areas.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Aerosol; Carbon; Oxygen; Plant physiology; Strontium; Sulfur

Multi-isotope fingerprints (O, Sr and Pb) in archaeological animal bone bioapatite: Similarity search and the suitability for provenance analysis in a geologically complex Alpine region - Tschetsch, L.; Mussauer, A.; Mauder, M.; Lohrer, J.; Kröger, P.; Mayr, Christoph; Söllner, F.; Grupe, G. (Archaeometry, 2020)
Multi-isotope fingerprints in the bioapatite of archaeological skeletons are mostly superior over single isotope analyses for provenance studies. Gaussian mixture model (GMM) clustering is a novel tool for a similarity search among multidimensional data sets and at the same time permits the evaluation of the structural importance of particular isotopic ratios in the data set. We applied three GMM clustering experiments on multi-isotope fingerprints—stable strontium (Sr), lead (Pb) and oxygen (O) isotopic ratios—established in 217 archaeological animal bones excavated along a specific transect across the European Alps. This reference region had been in use since prehistoric times by humans who crossed the Alps from north to south, and vice versa. The resulting clusters permit a spatial assignment of the specimens with a very high probability, in particular with regard to the geological complexity of the region. A combination of Sr with Pb stable isotopes led to an optimal differentiation between the southern and northern Alpine forelands that cannot be distinguished from each other by 87Sr/86Sr ratios alone, while the contribution of δ18O is not particularly high. The isotopic mapping and subsequent cluster analysis is suitable for the analysis of archaeological human finds and the reconstruction of the direction of transalpine mobility and trade.
CRIS-Team Scopus Importer:2020-03-27
Keywords: bone bioapatite; GMM clustering; multi-isotope fingerprint; provenance

Nesseltalgraben, a new reference section of the last glacial period in southern Germany - Mayr, Christoph; Brandlmeier, Birgit; Diersche, Volker; Stojakowits, Philipp; Kirscher, Uwe; Matzke-Karasz, Renate; Bachtadse, Valerian; Eigler, Michael; Haas, Ulrich; Lempe, Bernhard; Reimer, Paula; Spötl, Christoph (Journal of Paleolimnology, 2017)

New araphid species of the genus Pseudostaurosira (Bacillariophyceae) from southern Patagonia - García, M. Luján; Bustos, Sabrina; Villacís, Leonardo A.; Laprida, Cecilia; Mayr, Christoph; Moreno, Patricio I.; Maidana, Nora I.; Morales, Eduardo A. (European Journal of Phycology, 2021)
We describe five new araphid diatom species belonging to the genus Pseudostaurosira. These new taxa were found in modern and fossil material collected from five southern Patagonian waterbodies (49–52°S), four from the Santa Cruz province, Argentina and one from the Magallanes Region, Chile. When observed under light and scanning electron microscopy, each species differs by a single or a combination of valve character(s). Pseudostaurosira australopatagonica sp. nov. has unique volae that are profusely, dichotomously branched, internally anastomosed, and affixed to the virgae. Pseudostaurosira hyalopatagonica sp. nov. has fusiform valves with cuneate, elongate ends, narrow valves and round to slightly elliptical areolae. Pseudostaurosira catalinae sp. nov. has broadly fusiform valves with cuneate to subrostrate ends; volae form a circular to elliptical ring at the centre of the areolar opening and, externally covering the mantle areolae, it has a watch glass-like flap. Pseudostaurosira tehuelcheana sp. nov. has lanceolate valves with broadly rounded apices, solid incipient conical spines and marginal, transapically elongate areolae occluded by profusely branched volae. Pseudostaurosira zolitschkae sp. nov. is a relatively large-valve species with subrostrate apices, hollow spines, marginal areolae sometimes separated by a thin vimen. The volae in this latter, new taxon, only originate from a position parallel to the transapical axis of the valve, an origin that is uncommon within the genus. We discuss the validity of describing species based on morphological data and highlight the importance of increasing taxonomic resolution on isolated regions such as Patagonia.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Araphids; Fragilariaceae; non-marine; palaeolimnology; southernmost South America; taxonomy; valve ultrastructure

New gastropod assemblages from the Early/Middle Miocene of Riedensheim and Adelschlag-Fasanerie, southern Germany - Salvador, Rodrigo B.; Prieto, Jérôme; Mayr, Christoph; Rasser, Michael (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2016)

New Miocene record of the suid Listriodon near Munich - Prieto, Jérôme; Mayr, Christoph (Zitteliana, 2017)

No evidence for carryover effect in tree rings based on a pulse-labelling experiment on Juniperus communis in South Germany - He, Minhui; Bräuning, Achim; Rossi, Sergio; Gebrekirstos, Aster; Grießinger, Jussi; Mayr, Christoph; Peng, Changhui; Yang, Bao (Trees-Structure and Function, 2020)
Key message: A clear carryover effect of tree-ring formation was not detected based on a pulse-labelling experiment conducted on Juniperus communis in South Germany. Abstract: The inherent linkage between photosynthesis and the formation of wood is important for the understanding of relationships between tree-ring series and climate/environmental data in dendroclimatology studies. However, it is impossible to reach a mechanistic procedure of tree stem radial growth depending on its carbon balance from a traditional statistical point of view alone. Pulse labelling experiment with stable carbon isotope (13CO2) has provided innovative insights into the fate of recently assimilated carbon in organs and carbon-containing compounds. In this study, we conducted an in situ pulse labelling experiment on 27 July 2016 to examine the response of tree ring and different-aged needles to short-term elevated 13CO2 of a juniper shrub growing on a heathland in South Germany. New and old needles from four expositions were sampled before and after the experiment. A wood segment was taken from the main branch and stable carbon isotope composition (δ13C) was analysed at an intra-annual time scale. Before the experiment, the mean δ13C was − 26.8 ± 0.4‰ (mean ± standard deviation) for both needle ages, while woody tissue showed about 3‰ higher δ13C compared to needles. Substantial enriched 13C was detected in the needles after the experiment. New needles showed significant higher δ13C than the old ones 1–7 days after the experiment. Significant enriched δ13C was detected in the wood from 35 to 61% of the annual tree ring in 2016, indicating that the short-term enrichment of 13C can affect wood formation for a large section. No enhancement in 13C signal appeared in the tree ring of the subsequent year 2017, suggesting the absence of a carryover effect. Wood formation did not reply on the carbohydrates stored even 1 year before and thus tree-ring ecophysiological modelling as well as dendrochronological studies should therefore benefit from such result.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Carryover effect; Dendrochronology; Needle ages; Shrub species; Stable carbon isotope

Oxygen isotope ratios (18O/16O) of hemicellulose-derived sugar biomarkers in plants, soils and sediments as paleoclimate proxy I: Insight from a climate chamber experiment - Zech, Michael; Mayr, Christoph; Tuthorn, Mario; Leiber-Sauheitl, Katharina; Glaser, Bruno (Geochimica Et Cosmochimica Acta, 2014)

Oxygen isotope ratios of chironomids, aquatic macrophytes and ostracods for lake-water isotopic reconstructions - Results of a calibration study in Patagonia - Mayr, Christoph; Laprida, Cecilia; Lücke, Andreas; Martìn, Rodrigo; Massaferro, Julieta; Ramón-Mercau, Josefina; Wissel, Holger (Journal of Hydrology, 2015)
Oxygen stable isotopes (δ18O) of biogenic sedimentary components from lake sediment archives, such as ostracod valves, are frequently used for palaeoclimatic reconstructions. However, the effects of host water isotope changes, temperature-dependent fractionations, and vital effects on the isotopic ratios of such biogenic proxies often cannot be disentangled. Here, δ18O values of ostracod valves, head capsules of chironomid larvae and aquatic macrophyte cellulose from various lake and stream sites in southern Patagonia (41–52°S) are compared with δ18O values of their host waters. The best correlation between δ18O values of bioproxy and host water was obtained for aquatic cellulose exhibiting a slope of the regression of almost unity. Chironomid head capsules showed a strong correlation, but the data set was rather small (seven sites). The δ18O values of ostracod valves showed strong inter-specific vital effects. Strong offsets of ostracod values from isotopic equilibrium are possibly explained by re-working of subfossil valves, seasonality effects or different chemical composition of host waters. A weak, but significant temperature dependency of oxygen isotope fractionation was observed for cellulose of one aquatic taxon (Myriophyllum) and for ostracod calcite, but not for chironomids and aquatic moss cellulose. The present dataset suggests that δ18O values of aquatic cellulose are the most reliable proxy for host water isotope reconstructions, but clearly more investigations are needed to substantiate this finding.

Palaeoenvironments during MIS 3 and MIS 2 inferred from lacustrine intercalations in the loess-palaeosol sequence at Bobingen (southern Germany) - Mayr, Christoph; Matzke-Karasz, Renate; Stojakowits, Philipp; Lowick, Sally; Zolitschka, Bernd; Heigl, Tanja; Mollath, Richard; Theuerkauf, Marian; Weckend, Marc-Oliver; Bäumler, Rupert; Gregor, Hans-Joachim (E&G : Quaternary Science Journal, 2017)

Paleoenvironmental conditions define current sustainability of microbial populations in Laguna Potrok Aike sediments, Argentina - Vuillemin, Aurèle; Ariztegui, Daniel; Lücke, Andreas; Mayr, Christoph (Aquatic Sciences, 2014)

Recent decadal drought reverts warming-triggered growth enhancement in contrasting climates in the southern Andes tree line - Fajardo, Alex; Gazol, Antonio; Mayr, Christoph; Camarero, J. Julio (Journal of Biogeography, 2019)
Aims: Rising temperature and declining summer precipitation due to the 1970s-climate shift in southern South America have reduced forest productivity at dry sites. Here, we worked with the most widespread Southern Hemisphere tree line species, Nothofagus pumilio, across contrasting climatic conditions and determined whether rising atmospheric CO2 concentrations as well as warmer and drier climatic conditions provoked by the 70s-climatic shift have been causing systematic changes in tree line growth rates and intrinsic water-use efficiency (iWUE). Location: 36–54°S, southern Andes. Time period: 1950–2010. Major taxa studied: Nothofagus pumilio. Methods: We worked at five disparate climatic tree line locations, spanning 18 degrees of latitude; at each location, we sampled trees at four different elevations, including tree line elevation. We quantified the variation in annual tree-ring width (TRW) as a function of climate, elevation, tree age, size, annual CO2 concentrations and location, using linear mixed-effects models and interpreted TRW trends in relation to iWUE and isotope (δ13C and δ18O) signalling. Results: Across locations, the patterns of tree line growth occurring in the 1980–2010 period exhibited a clear and significant negative trend, in contrast to the previous 1950–1980 period. We found an increase in iWUE and δ18O across time and locations. Given that an increase in δ18O indicates a decrease in stomatal conductance, we assert that drought-induced stomatal closure appears to be causing the reduction in growth. Main conclusions: We show unequivocal evidence that warmer and drier summer conditions translated into a decrease in growth rates along the elevational tree line of the southern Andes, reverting previous growth improvements linked to climate warming. An improvement in iWUE at all locations is most likely explained by decreased stomatal conductance given the rising δ18O signal. An iWUE–growth decoupling may act as an ecological strategy to respond to drought.
CRIS-Team Scopus Importer:2019-06-18
Keywords: carbon isotopes; climate change; Nothofagus pumilio; oxygen isotopes; Patagonia; plant–climate interactions; tree rings; water-use efficiency

Reconstructing past variations in environmental conditions and paleoproductivity over the last ∼8000 years off north-central Chile (30°S) - Munoz, Praxedes; Rebolledo, Lorena; Dezileau, Laurent; Maldonado, Antonio; Mayr, Christoph; Cárdenas, Paola; Lange, Carina B.; Lalangui, Katherine; Sanchez, Gloria; Salamanca, Marco; Araya, Karen; Jara, Ignacio; et al. (Biogeosciences, 2020)
The aim of this project was to establish past variations in the main oceanographic and climatic features of a transitional semiarid ecosystem on the north-central Chilean coast. We analyzed recent sedimentary records retrieved from two bays, Guanaqueros and Tongoy (30° S), for geochemical and biological analyses, including the following: Sensitive redox trace elements, biogenic opal, total organic carbon (TOC), diatoms and stable isotopes of organic carbon and nitrogen. Three remarkable periods were established with different environmental conditions and productivities: (1) >6600 cal BP, (2) 4500-1800 cal BP and (3) 140 cal BP to the present (2015 CE). The first period was characterized by a remarkably higher productivity (higher diatom abundances and opal) in which large fluxes of organic compounds were also inferred from the accumulation of elements, such as Ba, Ca, Ni, Cd and P, in the sediments. Meanwhile, significantly reduced conditions at the bottom of the bays were suggested based on the large accumulation of Mo, Re and U, showing a peak at 6600 cal BP, when sulfidic conditions could have been present. According to the pollen moisture index (PMI), this was also identified as the driest interval. These conditions should be associated with an intensification of the Southern Pacific Subtropical Anticyclone (SPSA) and stronger southerly western winds, emulating La Ninãlike conditions, as has been described for the SE Pacific during the early Holocene and part of the mid-Holocene. During most of the second period, lower productivity was observed; however, a small increase was identified between 3400 and 4000 cal BP, although lower amounts of diatom (valves g-1) and nutrient-type metal accumulations were evident. Anoxic conditions at the bottom of the bays changed to an almost stable suboxic condition during this time interval. The third period was marked by intense oxygenation after 1800 cal BP, as observed by a drastic change in the accumulation of U, Mo and Re. This was followed by a return to more reduced conditions over the past 2 centuries, characterized by a small productivity rise after ∼ 140 cal BP, as suggested by the opal accumulations. Overall, lower primary productivity, lower reduced conditions at the bottom and higher-humidity conditions were established after 6600 cal BP to the present. We suggest that the oxygenation might be associated with a weak effect from the oxygen minimum zone over the shelf and intensified El Nino activity, introducing oxygenated waters to the coastal zones through the propagation of equatorial waves and establishment of conditions that reduced the primary productivity from the mid-Holocene toward the beginning of the modern era.
CRIS-Team Scopus Importer:2020-12-11

Refining the Late Quaternary tephrochronology for southern South America using the Laguna Potrok Aike sedimentary record - Smith, Rebecca E.; Smith, Victoria C.; Fontijn, Karen; Gebhardt, A. Catalina; Wastegård, Stefan; Zolitschka, Bernd; Ohlendorf, Christian; Stern, Charles; Mayr, Christoph (Quaternary Science Reviews, 2019)
This paper presents a detailed record of volcanism extending back to ∼80 kyr BP for southern South America using the sediments of Laguna Potrok Aike (ICDP expedition 5022; Potrok Aike Maar Lake Sediment Archive Drilling Project - PASADO). Our analysis of tephra includes the morphology of glass, the mineral componentry, the abundance of glass-shards, lithics and minerals, and the composition of glass-shards in relation to the stratigraphy. Firstly, a reference database of glass compositions of known eruptions in the region was created to enable robust tephra correlations. This includes data published elsewhere, in addition to new glass-shard analyses of proximal tephra deposits from Hudson (eruption units H1 and H2), Aguilera (A1), Reclus (R1, R2-3), Mt Burney (MB1, MB2, MBx, MB1910) and historical Lautaro/Viedma deposits. The analysis of the ninety-four tephra layers observed in the Laguna Potrok Aike sedimentary sequence reveals that twenty-five tephra deposits in the record are the result of primary fallout and are sourced from at least three different volcanoes in the Austral Andean Volcanic Zone (Mt Burney, Reclus, Lautaro/Viedma) and one in the southernmost Southern Volcanic Zone (Hudson). One new correlation to the widespread H1 eruption from Hudson volcano at 8.7 (8.6–9.0) cal ka BP during the Quaternary is identified. The identification of sixty-five discrete deposits that were predominantly volcanic ashes (glass and minerals) with subtle characteristics of reworking (in addition to three likely reworked tephra, and one unknown layer) indicates that care must be taken in the analysis of both visible and invisible tephra layers to decipher their emplacement mechanisms.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Geochemistry; Lacustrine; PASADO; Patagonia; Quaternary; South America; Stratigraphy; Tephrochronology; Volcanic ash

Responses of nitrogen and carbon deposition rates in Comau Fjord (42°S, southern Chile) to natural and anthropogenic impacts during the last century - Mayr, Christoph; Rebolledo, Lorena; Schulte, Katharina; Schuster, Astrid; Zolitschka, Bernd; Försterra, Günter; Häussermann, Verena (Continental Shelf Research, 2014)

Responses of testate amoebae assemblages (Amoebozoa: Arcellinida) to recent volcanic eruptions, inferred from the sediment record in Laguna Verde, southern Patagonia, Argentina - Charqueno-Celis, Fernanda; Sigala, Itzel; Zolitschka, Bernd; Perez, Liseth; Mayr, Christoph; Massaferro, Julieta (Journal of Paleolimnology, 2021)
There is little knowledge about testate amoebae in lakes and their responses to volcanic eruptions. To address this knowledge gap, we studied the paleoecology of these protists in a sediment record from Laguna Verde, a lake located east of the southern Patagonian Ice Field, in Santa Cruz Province, Argentina. The lake is under the influence of volcanic eruptions from Lautaro Volcano, Chile, similar to 42 km WNW of Laguna Verde. We evaluated the response of 11 testate amoeba morphospecies in the lake to the last four Lautaro eruptions, using a 61-cm sediment core. Calcium (Ca), a major element of volcanic ash, was the most important variable explaining testate amoeba variability in the three zones determined by detretended correspondence analysis. We identified four declines in testate amoeba abundance and diversity associated with tephra deposition. Poisson regression analysis revealed that Difflugia immanata, D. bidens, and D. glans strain "glans" decrease after deposition of tephra layers. In contrast, Centropyxis constricta strain "constricta," C. aculeata strain "aculeata" and Zivkovicia compressa respond positively to ash deposition. Our findings suggest a high resilience of testate amoebae to stochastic events such as volcanism because the same assemblage (D. immanata, D. bidens, and D. glans strain "glans") inhabited the lake before and after the ashfalls. Nevertheless, several volcanic eruptions during the last similar to 300 years may have weakened this resilience and had a long-term effect on community diversity. Multivariate analysis showed that potassium (K) plays a significant role in shaping assemblage composition. Because of the low K content of the Lautaro tephra, we infer that higher potassium concentrations in sediments are not related with volcanic events, but rather, are associated with terrestrial input. Future studies, however, will be needed to identify the source of K in the sediment record and its relationship with testate amoebae assemblages. Our study demonstrates the potential for using lacustrine testate amoebae as environmental proxies, and illustrates the direct effects of volcanic ash deposition on their assemblage composition, diversity and distribution in southern Patagonia.
CRIS-Team WoS Importer:2021-12-03

Seasonal climate variations during Marine Isotope Stages 3 and 2 inferred from high-resolution oxygen isotope ratios in horse tooth enamel from Lower Austria - Reiss, Lilian; Mayr, Christoph; Pasda, Kerstin; Joachimski, Michael; Einwögerer, Thomas; Händel, Marc; Maier, Andreas (Journal of Quaternary Science, 2024)
We present sequential oxygen isotope records (δ18Ophosphate vs. VSMOW) of horse tooth enamel phosphate of six individuals from two adjacent Palaeolithic sites in Lower Austria. Three molars from the site Krems-Wachtberg date to 33–31k cal a bp, and three molars from Kammern-Grubgraben to 24–20k cal a bp. All teeth show seasonal isotope variations, which are used to reconstruct the annual oxygen isotope composition of drinking water (δ18Odw) and palaeotemperatures. Measured δ18Ophosphate values ranged from 8.6 to 13.0‰ and from 10.8 to 13.9‰ at Krems-Wachtberg and Kammern-Grubgraben, respectively. An inverse modelling approach was used to reconstruct summer and winter temperatures after a correction for glacial oceanic source water δ18O. Reconstructed annual δ18Odw was −16.4 ± 1.5‰ at Krems-Wachtberg and −15.3 ± 1.4‰ at Kammern-Grubgraben, resulting in annual temperatures of −5.7 ± 3.1 and −3.5 ± 2.9°C, respectively. Summer and winter temperatures reconstructed from individual teeth exhibit high seasonal variations with moderate summer temperatures and extremely low winter temperatures typical for a polar tundra climate. Isotopic differences between individuals are attributed to interannual climate variability or to different drinking water sources. Our reconstructed temperatures are, overall, consistent with previously reported values from European horse teeth, when taking regional differences into account. <br
Keywords: δ18O; last glacial maximum; palaeotemperatures; phosphate; seasonality; sequential sampling; Upper Palaeolithic

Sea spray correction in δ13Ccarbonate, δ18Ocarbonate, δ18Ophosphate, and δ34Scollagen values of coastal humans - A methodological approach - Göhring, Andrea; Mayr, Christoph; Grupe, Gisela (Science of the Total Environment, 2020)
The so-called sea spray effect influences animals and humans living in coastal regions. As a consequence, δ13Ccarbonate, δ18Ocarbonate, δ18Ophosphate, and δ34Scollagen isotope values of affected individuals are more positive than otherwise expected. However, the effect is hidden in the case of humans who actually might have consumed marine food what would (partly) explain their isotopic signature. In order to correct for the sea spray effect in humans the dietary proportions were calculated based on the δ13Ccollagen and δ15Ncollagen isotope values using stable isotope mixing models. Four different programs (SISUS, simmr, IsotopeR, MixSIAR) were applied which resulted in quite different calculated diets. Each individual human can be corrected for the sea spray effect using the calculated proportion of terrestrial food (e.g. domesticated mammals, plants) and the approximated sea spray effect for each isotopic system. The differences in the calculated food proportions detected for the different mixing model programs, however, lead to differences in the correction procedure. We suggest using the dietary proportions as obtained by probabilistic SISUS rather than those of the Bayesian programs (simmr, IsotopeR, MixSIAR). The correction against the sea spray effect using the dietary proportions calculated by SISUS was supported by Gaussian Mixture Model (GMM) clustering which also enables the identification of probably non-local individuals in the dataset.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Aerosol; Archaeometry; Bone; Cluster analysis; Diet

Significance and Limitations of Stable Oxygen Isotope Ratios in the Apatite Phosphate of Archaeological Vertebrate Finds for Provenance Analysis in an Alpine Reference Region - Mauder, M.; Ntoutsi, E.; Kroeger, P.; Mayr, Christoph; Toncala, A.; Hoelzl, S.; Grupe, G. (Archaeometry, 2019)
A multi-isotope fingerprint consisting of delta O-18(phosphate), Sr-87/Sr-86, Pb-208/Pb-204, Pb-207/Pb-204, Pb-206/Pb-204, Pb-208/Pb-207 and Pb-206/Pb-207 was established in the bioapatite of 219 individual archaeofaunal remains (cattle, pig, red deer) excavated from sites located along a specific transect of the European Alps, namely the Inn-Eisack-Adige-Brenner Passage, that has been of eminent importance since European prehistory. This reference area is vertically stratified, and since delta O-18 in the skeleton is influenced by climate, water source, physiology and even culture, we tested the relative contribution and importance of delta O-18 as a component of the multi-isotope fingerprint for provenance analysis in this alpine region by a novel mathematical approach. In particular, we adapted a supervised learning approach through expectation-maximization (EM) clustering for fingerprint extraction and evaluated the contribution of each isotopic ratio to the data structure. While an altitude effect was evident in delta O-18, its overall structural importance in the complete isotopic fingerprint was rather low. Therefore, provenance analysis of bioarchaeological finds in this region is possible by measuring stable Sr and Pb ratios alone, which is of considerable importance when delta O-18 values are not available, e.g., in cremated finds, although some information is lost. Whether this is tolerable depends on the scientific question to be solved.
CRIS-Team WoS Importer:2019-02-21

Southern Hemispheric Westerlies control sedimentary processes of Laguna Azul (south-eastern Patagonia, Argentina) - Zolitschka, Bernd; Fey, Michael; Janssen, Stephanie; Maidana, Nora I.; Mayr, Christoph; Wulf, Sabine; Haberzettl, Torsten; Corbella, Hugo; Luecke, Andreas; Ohlendorf, Christian; Schaebitz, Frank (Holocene, 2019)
Multiproxy investigations of lacustrine sediments from Laguna Azul (52 degrees S) document multi-millennial Holocene influences of Southern Hemispheric Westerlies (SHW) on the hydroclimatic variability of south-eastern Patagonia. During the last 4000 years, this hydroclimatic variability is overprinted by centennial warm/dry periods. A cool/wet period from 11,600 to 10,100 cal. BP is succeeded by an early Holocene dry period (10,100-8300 cal. BP) with a shallow lake, strong anoxia, methanogenesis and high salinity. Between 8300 and 4000 cal. BP the influence of SHW weakened, resulting in a freshwater lake considered to be related to less arid conditions. Since 4000 cal. BP, regional temperature decreased accompanied by re-intensification of SHW reaching full strength since 3000 cal. BP. Centred around 2200, 1000 cal. BP and in the 20th century, Laguna Azul experienced century-long warm/dry spells. Between these dry periods, two pronounced moist periods are suggested to be contemporaneous to the Dark Age Cold Period' and the Little Ice Age'. Different from millennial SHW variations, centennial fluctuations appear to be synchronous for South America and the Northern Hemisphere. Changes in solar activity, large volcanic eruptions and/or modulations of ocean circulation are potential triggers for this synchronicity.
CRIS-Team WoS Importer:2019-04-02

Stable isotope records of sei whale baleens from Chilean Patagonia as archives for feeding and migration behavior - Reiss, Lilian; Häussermann, Verena; Mayr, Christoph (Ecology and Evolution, 2019)
Carbon (δ13C) and nitrogen (δ15N) stable isotope variations in baleen plates of sei whales (Balaenoptera borealis) stranded after a mass mortality event in Chilean Patagonia were investigated to assess potential dietary and migratory patterns. Carbon and nitrogen isotope ratios of seven baleens from six individuals were analyzed. The δ13C values ranged from − 19.1 to − 15.9‰ and the δ15N values from 8.7 to 15.4‰. Variations of up to 2.9‰ for δ13C and 5.3‰ for δ15N were observed within one baleen. Carbon and nitrogen isotope records of each baleen were significantly correlated and showed recurring oscillations confirmed by wavelet analyses. Oscillations slightly differed in periodicity indicating variable baleen growth rates between 10.0 and 16.5 cm/year. Food sources of the whales are discussed in terms of available isotope data for potential prey taxa and potential migratory behavior on the basis of latitudinal isotope gradients of particulate organic matter. Cyclicity could be explained by regular migrations of the sei whales from subtropical calving areas to high-latitude foraging grounds. δ15N records of baleens differed between individuals eventually pointing to diverse feeding and migratory preferences among sei whale individuals.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Balaenoptera borealis; baleen growth rate; carbon isotopes; mass mortality event; nitrogen isotopes; Patagonian fjords

Stable isotope relationships between apatite phosphate (δ18 O), structural carbonate (δ18 O, δ13 C), and collagen (δ2 H, δ13 C, δ15 N, δ34 S) in modern human dentine - Lehn, Christine; Rossmann, Andreas; Mayr, Christoph (Rapid Communications in Mass Spectrometry, 2020)
RATIONALE: The use of multi-isotopic analysis (δ2 H, δ13 C, δ15 N, δ18 O, and δ34 S values) of modern human body tissues for provenancing of unknown individuals in forensics is increasing. Tooth dentine develops during childhood and adolescence, therefore providing geographical information from that period of life. Tooth apatite δ18 O values are commonly used for the reconstruction of drinking water values, and H-C-N-S isotope ratios in collagen supply additional information about the composition of diet. We tested if dentine collagen δ2 H values provide similar information to apatite δ18 O values with a proof-of-concept study. METHODS: Tooth samples were taken from modern-day individuals born in different regions of the world. Apatite and collagen were prepared from dentine. Stable isotope analyses were performed on apatite phosphate oxygen (δ18 Ophos ); oxygen and carbon of the structural carbonate (δ18 Ocarb , δ13 Ccarb ); and hydrogen, carbon, nitrogen, and sulfur of the collagen (δ2 Hcoll, δ13 Ccoll , δ15 N, δ34 S). RESULTS: δ18 Ophos , δ18 Ocarb , and δ2 Hcoll values are highly correlated in modern human dentine. There are significant relationships of δ18 O values in the apatite fraction and δ2 H values in the collagen fraction with local δ18 O and δ2 H precipitation values, respectively. Pearson correlation coefficients indicate no direct relationship between δ15 N values and the isotope ratios of any other element. Weak relationships exist between collagen δ34 S values and δ18 Ocarb or δ18 Ophos values. CONCLUSIONS: The highly significant correlation of δ18 Ophos , δ18 Ocarb , and δ2 Hcoll values in the modern human dentine implies that measurement of δ2 H values in collagen or δ18 O values in bioapatite will provide reliable information about the climate at the person's whereabouts.
CRIS-Team Scopus Importer:2020-03-17

The Concept of Isotopic Landscapes: Modern Ecogeochemistry versus Bioarchaeology - Grupe, Gisela; Hölzl, Stefan; Mayr, Christoph; Söllner, Frank (Across the Alps in Prehistory, 2017)

The Greidaloch near Murnau in the northern Estergebirge in the Bavarian Alps Das Greidaloch bei Murnau im nördlichen Estergebirge, Bayerische Alpen - Wolf, Andreas; López Correa, Matthias; al-Fudhaili, Najat; Rupp, Hildegard; Mayr, Christoph; Pasda, Kerstin (Mitteilungen des Verbandes der Deutschen Höhlen- und Karstforscher, 2021)
The 38 m deep and 55 m long pit cave Greidaloch (1272/05) has been discovered in 1994 in the northwestern part of the Estergebirge in the Bavarian Alps. The entrance at 1431 m a.s.l. is located 3 km SE of Murnau on the southern slope of the Buchrain and is developed along local NNE-SSW striking faults within folded carbonates of the Triassic Plattenkalk unit. Here, the survey of the cave is given together with a detailed description. At the deepest point, the bones of an adult male red deer (Cervus elaphus) have been found, along with bones of other vertebrates, notably the skull of a European Woodcock (Scolopax rusticola), and rests of a Common Hazelhen (Tetrastes bonasia). 14C-dating revealed an early Holocene age for the deer at 10.3 calibrated kiloyears before present (ka cal BP).
CRIS-Team Scopus Importer:2024-12-16

The Laschamps geomagnetic excursion recorded in continental sediments from southern Germany - Kirscher, U.; Dallanave, E.; Weissbrodt, V.; Stojakowits, P.; Grau, Michael; Bachtadse, V.; Mayr, Christoph (Geophysical Journal International, 2021)
We present palaeo- A nd rock magnetic results from a well-dated, 21 m-thick, Late Pleistocene continental sedimentary section located in southern Germany. Rock magnetic measurements reveal a complex magnetic mineralogy dominated by low coercivity minerals likely related to single domain biogenic magnetite and biogenic or early diagenetic greigite. In the lower part of the section also detrital haematite is present. The stable remanence shows predominantly normal polarity with two marked deviations at ∼1280-1200 cm and at 886 cm profile depth. Whereas the lower excursion is well established by several samples and documented also by detrital haematite, the upper one is only represented by a single sample and revealed by magnetite and greigite. Using the radiocarbon-based age model for the section, the lower excursion yields an age of 42.8-41.3 ka cal BP and is interpreted to represent the Laschamps geomagnetic excursion. The increased abundance of greigite in the upper part of the section, especially in the sample responsible for the upper anomalous direction, renders the interpretation of an actual excursion problematic due to the reducing environment necessary for the greigite formation.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Europe; Geomagnetic excursions; Palaeomagnetism; Rock and mineral magnetism

The last glacial maximum in Europe – State of the Art in Geoscience and Archaeology - Maier, Andreas; Mayr, Christoph; Peresani, Marco (Quaternary international, 2021)
CRIS-Team Scopus Importer:2021-03-26

The paleolimnologist's guide to compound-specific stable isotope analysis - An introduction to principles and applications of CSIA for Quaternary lake sediments - Holtvoeth, Jens; Whiteside, Jessica H.; Engels, Stefan; Freitas, Felipe S.; Grice, Kliti; Greenwood, Paul; Johnson, Sean; Kendall, Iain; Lengger, Sabine K.; Luecke, Andreas; Mayr, Christoph; Naafs, B. David A.; et al. (Quaternary Science Reviews, 2019)
The stable isotope composition of key chemical elements for life on Earth (e.g., carbon, hydrogen, nitrogen, oxygen, sulfur) tracks changes in fluxes and turnover of these elements in the biogeosphere. Over the past 15-20 years, the potential to measure these isotopic compositions for individual, source-specific organic molecules (biomarkers) and to link them to a range of environmental conditions and processes has been unlocked and amplified by increasingly sensitive, affordable and wide-spread analytical technology. Paleoenvironmental research has seen enormous step-changes in our understanding of past ecosystem dynamics. Vital to these paradigm shifts is the need for well-constrained modern and recent analogues. Through increased understanding of these environments and their biological pathways we can successfully unravel past climatic changes and associated ecosystem adaption. With this review, we aim to introduce scientists working in the field of Quaternary paleolimnology to the tools that compound-specific isotope analysis (CSIA) provides for the gain of information on biogeochemical conditions in ancient environments. We provide information on fundamental principles and applications of novel and established CSIA applications based on the carbon, hydrogen, nitrogen, oxygen and sulfur isotopic composition of biomarkers. While biosynthesis, sources and associated isotope fractionation patterns of compounds such as n-alkanes are relatively well-constrained, new applications emerge from the increasing use of functionalized alkyl lipids, steroids, hopanoids, isoprenoids, GDGTs, pigments or cellulose. Biosynthesis and fractionation are not always fully understood. However, although analytical challenges remain, the future potential of deeper insights into ecosystem dynamics from the study of these compounds is also emerging. (C) 2019 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-04-02

Trace element and stable (C, O) and radiogenic (Sr) isotope geochemistry of stromatolitic carbonate rocks of the Mesoarchaean Pongola Supergroup: Implications for seawater composition - Siahi, Mehrnaz; Hofmann, Axel; Master, Sharad; Wilson, Allan; Mayr, Christoph (Chemical Geology, 2018)

Tree-ring δ18O records of abating June–July monsoon rainfall over the Himalayan region in the last 273 years - Singh, Jayendra; Singh, Nilendu; Chauhan, Pankaj; Yadav, Ram R.; Bräuning, Achim; Mayr, Christoph; Rastogi, Tanupriya (Quaternary international, 2019)
There are knowledge gaps in the long-term changes in Indian summer monsoon rainfall (ISMR, June–September) behaviour, which affects the livelihood of large population in the Indian subcontinent. To better understand ISMR variability, we reconstructed June–July rainfall for the period 1743–2015 CE from Dingad valley, Uttarakhand, central Himalaya using δ18O variations in tree rings. For this, regional mean tree-ring isotope chronology, prepared by merging δ18O chronologies of two conifer (Abies pindrow (Royle ex D.Don) Royle and Picea smithiana (Wall.) Boiss) and one broadleaf deciduous species (Aesculus indica (Wall. ex Camb.) Hook), was used. The reconstructed rainfall series revealed significant correlations with the observational monsoon records from different regions of India. The most conspicuous feature in our reconstructed series is a decreasing rainfall trend since 1743 CE with the driest period in the late 20th and early 21st centuries, which is consistent with other monsoon rainfall proxies from a large part of the south Asian monsoon region (India, Nepal, Bhutan, Myanmar and Tibet Plateau). Consistency of reconstructed series with instrumental records and proxies from different regions revealed the capture of regional scale rainfall features in our data testifying its utility in understanding ISMR variability in long-term perspective.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Climate reconstruction; Himalayan region; India; Indian summer monsoon rainfall; June–July rainfall; Oxygen isotope; Tree-ring

Unravelling climate change impacts from other anthropogenic influences in a subalpine lake: a multi-proxy sediment study from Oberer Soiernsee (Northern Alps, Germany) - Hofmann, Andrea M.; Kuefner, Wolfgang; Mayr, Christoph; Dubois, Nathalie; Geist, Juergen; Raeder, Uta (Hydrobiologia, 2021)
Mountain lakes are increasingly impacted by a series of both local and global disturbances. The present study reveals the eutrophication history of a remote subalpine lake (Oberer Soiernsee, Northern Alps, Germany), triggered by deforestation, alpine pasturing, hut construction, tourism and atmospheric deposition, and identifies the intertwined consequences of on-going global warming on the lake's ecosystem. The primary objective was to disentangle the various direct and indirect impacts of these multiple stressors via down-core analyses. Our multi-proxy approach included subfossil diatom assemblages, carbon and nitrogen stable isotope ratios and subfossil pigments from dated sediments. Shifts within the diatom assemblages were related to variations in trophic state, lake transparency, water temperature and thermal stratification. The organic carbon isotope (delta C-13(org)) records, the diatom valve density and the pigment concentrations documented the development of primary production and composition. Total nitrogen isotope values (delta N-15) are more likely to reflect the history of atmospheric nitrogen pollution than lake-internal processes, also mirrored by the decoupling of delta N-15 and delta C-13(org) trends. The composition of sedimentary pigments allowed a differentiation between planktonic and benthic primary production. Concordant trends of all indicators suggested that the lake ecosystem passed a climatic threshold promoted by local and long-distance atmospheric nutrient loadings.
CRIS-Team WoS Importer:2021-07-23

Using distributions and stable isotopes of n-alkanes to disentangle organic matter contributions to sediments of Laguna Potrok Aike, Argentina - Hockun, Katja; Mollenhauer, Gesine; Ho, Sze Ling; Hefter, Jens; Ohlendorf, Christian; Zolitschka, Bernd; Mayr, Christoph; Lücke, Andreas; Schefuß, Enno (Organic Geochemistry, 2016)

Validation of a coupled delta H-2(n-alkane)-delta O-18(sugar) paleohygrometer approach based on a climate chamber experiment - Hepp, Johannes; Mayr, Christoph; Rozanski, Kazimierz; Schaefer, Imke Kathrin; Tuthorn, Mario; Glaser, Bruno; Juchelka, Dieter; Stichler, Willibald; Zech, Roland; Zech, Michael (Biogeosciences, 2021)
The hydrogen isotope composition of leaf-wax-derived biomarkers, e.g., long-chain n-alkanes (delta H-2(n-alkane)), is widely applied in paleoclimate. However, a direct reconstruction of the isotope composition of source water based on delta H-2(n-alkane) alone is challenging due to the enrichment of heavy isotopes during evaporation. The coupling of delta H-2(n-alkane) with delta O-18 of hemicellulose-derived sugars (delta O-18(sugar)) has the potential to disentangle this limitation and additionally to allow relative humidity reconstructions. Here, we present delta H-2(n-alkane) as well as delta O-18(sugar) results obtained from leaves of Eucalyptus globulus, Vicia faba, and Brassica oleracea, which grew under controlled conditions. We addressed the questions of (i) whether delta H-2(n-alkane) and delta O-18(sugar) values allow reconstructions of leaf water isotope composition, (ii) how accurately the reconstructed leaf water isotope composition enables relative humidity (RH) reconstruction, and (iii) whether the coupling of delta H-2(n-alkane) and delta O-18(sugar) enables a robust source water calculation. For all investigated species, the n-alkane n-C-29 was most abundant and therefore used for compound-specific delta H-2 measurements. For Vicia faba, additionally the delta H-2 values of n-C-31 could be evaluated robustly. Regarding hemicellulose-derived monosaccharides, arabinose and xylose were most abundant, and their delta O-18 values were therefore used to calculate weighted mean leaf delta O-18(sugar) values.Both delta H-2(n-alkane) and delta O-18(sugar) yielded significant correlations with delta H-2(leaf water) and delta O-18(leaf water), respectively (r(2)=0.45 and 0.85, respectively; p<0.001, n=24). Mean fractionation factors between biomarkers and leaf water were found to be -156 parts per thousand (ranging from -133 parts per thousand to -192 parts per thousand) for epsilon(n-alkane/leaf water) and +27.3 parts per thousand (ranging from +23.0 parts per thousand to 32.3 parts per thousand) for epsilon(sugar/leaf water), respectively. Modeled RHair values from a Craig-Gordon model using measured Tair, delta 2Hleaf water and delta 18Oleaf water as input correlate highly significantly with modeled RHair values (R2=0.84, p<0.001, RMSE = 6 %). When coupling delta H-2(n-alkane) and delta O-18(sugar) values, the correlation of modeled RHair values with measured RHair values is weaker but still highly significant, with R-2=0.54 (p<0.001, RMSE = 10 %). Finally, the reconstructed source water isotope composition (delta H-2(s) and delta O-18(s)) as calculated from our coupled approach matches the source water in the climate chamber experiment (delta H-2(tank water) and delta O-18(tank water)). This highlights the great potential of the coupled delta H-2(n-alkane)-delta O-18(sugar) paleohygrometer approach for paleoclimate and relative humidity reconstructions.
CRIS-Team WoS Importer:2021-10-15